The Analysis Of Gesture Used By The Students Of English Study Program In The Classroom Interaction At The University Of Sembilanbelas November, Kolaka - Ainun Nur Farlianti; Roslina Roslina; Hariadi Syam (STAI Miftahul Ula Nganjuk, 2017)
This research investigated “The Analysis of Gesture Used by Students of English Study Program in the Classroom Interaction at University of Sembilanbelas November, Kolaka”. The research problems were: what kinds of gesture that used by the students in the classroom interaction? And what are the functions of gesture which used by the students? With the objective of the research were to figure out several kinds of gesture that the students used in the classroom and to find out functions of gesture which used by the students. The method that used of this research was The Descriptive-Qualitative Method. The instruments that used in this research, those were observation and interview. The research participants in this research was the students of English Study Program and amounted to about 30 students, the lesson, as schedule in the fourth semester was Speaking Class, at the University of Sembilanbelas November, Kolaka. The results of this research concluded that, there were 29 kinds of the gesture which used by the students in the classroom interaction. And the functions of gesture were used by the students was also variously. But the functions of gesture were used by the students almost all of them were same. It was to show the sign of the tough-minded and stubborn individual, the interest of the student in the conversation, the student was lacking in self-confidence, courtesy and good attitude, showed disagreement, showed self-controlling, authority when argue, the persons’ habitual, the persons’ forgetfulness, the person’s shy nature, the person’s confident, showed self, the person enthusiasm when respond something, showed the courtesy, to disguise nervousness, to illustrate numbers, to clarify, gave comment, to express kept the confidence, to express the student felt nervous and insecure.